Hemisynthesis of Pentacyclic Triterpenoids from Diospyros foxworthyi with In vitro and In silico Anti-malarial Evaluation - Abd Ghani, Muhammad S.; Abu Bakar, Nur A. L.; Ramadani, Arba Pramundita; Nugraha, Arde Toga; Awang, Khalijah Binti; Che Omar, Mohammad Tasyriq; Supratman, Unang; Kamarulzaman, Ezatul Ezleen; Mohamad Taib, Mohamad Nurul Azmi (Current Organic Chemistry, 2024)
A total of twelve pentacyclic triterpenoid derivatives based on betulin (1) and lupeol (2) scaffolds isolated from Diospyros foxworthyi were hemisynthesized by acylation or acetylation reactions with appropriate acid chloride or acetic anhydride. The structures of the hemisynthesised compounds were characterised by means of FT-IR, 1D- and 2D-NMR, as well as HRMS analysis. These compounds were assayed for in vitro anti-malarial studies by inhibition of β-hematin formation assay with chloroquine as a positive control. Compounds 1d and 2f showed the strongest potential as β-hematin formation inhibitors with IC50 values of 6.66 ± 1.36 and 11.89 ± 0.15 μM, respectively, compared with the positive control (chloroquine; IC50 = 37.50 ± 0.60 μM). In silico molecular docking simulations were performed using AutoDock Vina for compounds 1d and 2f to investigate the binding interactions and free energy of binding (FEB) with the hemozoin supercell crystal structure (CCDC number: XETXUP01). The findings revealed several hydrophobic interaction modes between the 1d, 2f and hemozoin, with calculated FEBs of -8.4 ± 0.2 and -8.9 ± 0.0 kcal mol-1, indicating strong and favourable interactions.
Keywords: β-hematin inhibition activity